The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-76727-6
|View full text |Cite
|
Sign up to set email alerts
|

3D X-ray tomographic analysis reveals how coesite is preserved in Muong Nong-type tektites

Abstract: Muong Nong-type (MN) tektites are a layered type of tektite associated to the Australasian strewn field, the youngest (790 kyr) and largest on Earth. In some MN tektites, coesite is observed in association with relict quartz and silica glass within inclusions surrounded by a froth layer. The formation of coesite-bearing frothy inclusions is here investigated through a 3D textural multiscale analysis of the vesicles contained in a MN tektite sample, combined with compositional and spectroscopic data. The vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Muong Nong tektites are also characterized, with respect to standard splashform australasites, by (1) a higher volatile content (water, noble gases, etc. ; see Koeberl 1992;Beran and Koeberl 1997;Mizote et al 2003); (2) the pressure of gas bubbles within the atmospheric range, while splashforms bubble pressure estimates suggest solidification outside the atmosphere (Mizote et al 2003;Z ak et al 2019); (3) the preservation of crystalline inclusions of coesite, cristobalite, zircon, and magnetite (Kleinman 1969;Glass and Barlow 1979;Cavosie et al 2018;Krizova et al 2019;Masotta et al 2020) indicative of lower peak temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Muong Nong tektites are also characterized, with respect to standard splashform australasites, by (1) a higher volatile content (water, noble gases, etc. ; see Koeberl 1992;Beran and Koeberl 1997;Mizote et al 2003); (2) the pressure of gas bubbles within the atmospheric range, while splashforms bubble pressure estimates suggest solidification outside the atmosphere (Mizote et al 2003;Z ak et al 2019); (3) the preservation of crystalline inclusions of coesite, cristobalite, zircon, and magnetite (Kleinman 1969;Glass and Barlow 1979;Cavosie et al 2018;Krizova et al 2019;Masotta et al 2020) indicative of lower peak temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Zr versus Sr plot for the studied pseudotektites (circles) as well as reference outcrops from the Philippines (diamonds; see Table 3); data for the Australasian tektites (black squares; both Muong Nong and splash form types) from the literature (Amare & Koeberl, 2006; Chapman & Schreiber, 1969; Masotta et al., 2020; Mizera et al., 2016; Son & Koeberl, 2005; Žak et al., 2019) are shown for comparison. [Color figure can be viewed at wileyonlinelibrary.com] …”
Section: Discussionmentioning
confidence: 99%
“…Total alkali silica (TAS) diagram (after Le Maitre, 2002) for pseudotektites (circles) based on ICP-AES (or electron micro-probe analyzer for sample 2200; see Tables1 and 2), and for geological references for the Philippine glasses afterReepmeyer et al (2011; green diamonds). Data for the Australasian tektites (black diamonds; both Muong Nong and splash form types) from the literature(Amare & Koeberl, 2006;Chapman & Schreiber, 1969;Masotta et al, 2020;Mizera et al, 2016;Son & Koeberl, 2005;Zak et al, 2019), as well as high Na/K australites (red triangles afterChapman & Schreiber, 1969) are shown for comparison. (Color figure can be viewed at wileyonlinelibrary.com.…”
mentioning
confidence: 99%
“…Because the MGC analysis of coesite was performed directly after the transformation from quartz, the random orientation of the crystals is consistent with the reconstructive nature of the quartz‐coesite transformation that should not induce any inherited LPO in the daughter crystals (Tolédano & Dmitriev, 1996). Recent studies have shown that in rare cases, such as during impacts, a crystallographic parent‐daughter relation can be preserved throughout the quartz‐coesite transition (Campanale et al., 2019; Glass et al., 2020; Masotta et al., 2020). However, the exact conditions required for such coherent orientation relationships, as well as the corresponding transformation mechanism, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that in rare cases, such as during impacts, a crystallographic parent-daughter relation can be preserved throughout the quartz-coesite transition (Campanale et al, 2019;Glass et al, 2020;Masotta et al, 2020). However, the exact conditions required for such coherent orientation relationships, as well as the corresponding transformation mechanism, remain unclear.…”
Section: Evolution Of Lpo Across the Coesite To Stishovite Transitionmentioning
confidence: 99%